Possibility of a new order parameter driven by multipolar moment and Fermi surface evolution in CeGe - Karan Singh (Nature Portfolio, 2019)
Abstract Polycrystalline CeGe is investigated by means of DC and AC susceptibility, non-linear DC susceptibility, electrical transport and heat capacity measurements in the low temperature regime. This compound shows two peaks at low magnetic field around T I ~ 10.7 and T II ~ 7.3 K due to antiferromagnetic ordering and subsequent spin rearrangement respectively. Investigation of non-linear DC susceptibility reveals a presence of higher order magnetization which results in the development of a new order parameter around T I. This leads to a lowering of symmetry of the magnetic state. The order parameter increases with decreasing temperature and stabilizes around T II. Consequently, the symmetry of the magnetic state is preserved below this transition. Heat capacity and resistivity results indicate the presence of a gap opening around T I on portion of Fermi surface, due to evolution of the Fermi surface. Magnetoresistance behavior and violation of Kohler’s rule suggest that the evolution of Fermi surface changes the symmetry of magnetic state. The observation of new order parameter (which is of second order) is also confirmed from the Landau free energy theory.